Efficacy of Jailed Semi-Inflated Balloon Technique in Maintaining Side Branch Patency during Percutaneous Coronary Intervention-A Novel Approach in Bifurcation Lesions - Abbas Jaffri, Syed Khawar; Mehboob Abbasi, Sardar Bilal (Indus Journal of Bioscience Research, 2025)
Background: Bifurcation lesions offer a major PCI complexity due to their involvement of the main vessel in addition to the side branch with considerable risk to side branch thrombosis. Objective: To evaluate the efficacy of the jailed semi-inflated balloon technique (JSBT) in maintaining side branch (SB) patency during percutaneous coronary intervention (PCI) for coronary bifurcation lesions. Material and methods: This Cross-sectional study was conducted at the Department of Cardiology, Armed Forces Institute of Cardiology/National Institute of Heart Disease (AFIC/NIHD), Rawalpindi from May 2024 to Dec 2024. Data were collected through the non-probability consecutive sampling technique. A detailed medical history was taken, during which baseline characteristics and comorbidities were meticulously documented. Results: Data were collected from 118 patients according to criteria of the study. The mean age in Group I (JSBT utilized) was 59.8 ± 9.8 years, while in Group II (JSBT not utilized) it was 58.7 ± 11.2 years. Gender distribution was similar between the groups, with 64.4% males and 35.6% females in Group I, and 62.7% males and 37.3% females in Group II. Mean number of vessels involved was 2.3 ± 0.6 in Group I (JSBT utilized) and 2.2 ± 0.5 in Group II (JSBT not utilized), with no significant difference (p=0.47). The culprit vessel was most commonly the left anterior descending (LAD) artery in both groups, accounting for 45.8% in Group I and 47.5% in Group II (p=0.87). Conclusion: This study concludes that the Jailed Semi-Inflated Balloon Technique (JSBT) is a highly effective method for maintaining side branch (SB) patency during percutaneous coronary intervention (PCI) in bifurcation lesions.